Post COVID Health Problems faced by COVID-19 Infected Healthcare Professionals of a Tertiary Level Hospital - Sapkota, Babita; Dhakal Chalise, Gita; Shrestha, Sarala (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: COVID-19 is an infectious disease which predominantly affects the lungs but it can also affect other organs such as gastro-intestinal system, brain, heart etc. The substantial proportion of infected people experience mild to moderate symptoms and recover with no after-effects. Some people with COVID- 19 can experience long term health problems, known as post-COVID health problems. These are inflammatory or host response towards virus that occurs after four weeks of initial infection and beyond. The aim of this study was to find out the post COVID health problems faced by COVID-19 infected healthcare professionals of a tertiary level hospital. Methods: This was a descriptive cross-sectional study carried out among healthcare professionals recovered from COVID-19 infection who were selected by using non -probability purposive sampling technique. A semi-structured self-administered questionnaire was used for data collection. The collected data were analyzed by using descriptive and inferential statistics. Results: Out of 108 healthcare professionals who participated in the study, 42.6% were experiencing various post-COVID health problems. These problems included fatigue (78.3%), persistent cough (54.3%), headache (37%), malaise (34.8%), body ache (32.6%) and others. No significant association of the experience of post- COVID health problems among respondents with their age, sex and COVID-19 vaccination status was revealed at 0.05 level of significance. Conclusions: A considerable proportion of health professionals are liable to experience various post-COVID health problems after being infected with COVID- 19. Their age, sex and COVID-19 vaccination status do not tend to influence on their post-COVID health problems.